`1/3+x=2/3+1/5`
`\ x=2/3-1/3+1/5`
`\ x=1/3+1/5`
`\ x=5/15+3/15`
`\ x=8/15`
Vậy `x=8/15`
\(\dfrac{1}{3}\) + x = \(\dfrac{2}{3}+\dfrac{1}{5}\)
\(\dfrac{1}{3}\) + x = \(\dfrac{13}{15}\)
x = \(\dfrac{13}{15}\) - \(\dfrac{1}{3}\)
x = \(\dfrac{8}{15}\)
Vậy x = \(\dfrac{8}{15}\)
\(a,\)\(\dfrac{1}{3}+x=\dfrac{2}{3}+\dfrac{1}{5}\)\(\Rightarrow x=\dfrac{2}{3}+\dfrac{1}{5}-\dfrac{1}{3}=\dfrac{8}{15}\)
\(b,\)\(\dfrac{3}{7}:x=\dfrac{15}{4}\Rightarrow\dfrac{3}{7x}=\dfrac{15}{4}\Rightarrow x=\dfrac{\dfrac{3.4}{15}}{7}=\dfrac{4}{35}\)